Analysis of symmetrical components and balanced earth faults in distribution transformers - Munoz, Roberto Pfuyo (2022)
The objective of this study is to show the analysis and behavior of symmetrical components and balanced faults in power transformers. Thus, the symmetric component methods solve directly the distribution of voltages and currents, allowing the correct verification of the procedure and the influence of earth circuit faults with the neutral point in distribution transformers. Therefore, the symmetric component analysis procedure has an innovative contribution to the determination of problem solving that solves practical cases and allows to determine the unbalanced failure analysis.